Role of Vitamin E on Antispermatogenic Effects of Indomethacin on Number of Sperm Containing Seminiferous Tubules of Testes in Long Evans Rats (Bangladesh Journal of Anatomy, 2009)
Context: Indomethacin is the most commonly and widely used nonsteroidal antiinflammatory analgesic and antipyretic drug. Despite its effectiveness as an antiinflammatory use, indomethacin causes inhibition of spermatogenesis leading to infertility. On the other hand, vitamin E enhances spermatogenesis. Therefore, the present study was designed to observe the protective role of vitamin E on indomethacin induced testicular damage. Objective: To observe the effects of vitamin E on indomethacin induced testicular damage in Long Evans rats. Study design: An experimental study. Place and period of study: The study was carried out in the Department of Anatomy, Sir Salimullah Medical College, Dhaka. Materials and methods: Eightyfour mature Long Evans male rats were divided into four groups (I, II, III and IV). The rats of group I, II and III were treated with indomethacin at different doses and duration. Group IV rats were treated with indomethacin and vitamin E at different doses for 49 days. Histologically the number of sperm containing and nonsperm containing seminiferous tubules were counted. Results: There was significant reduction (P